Pemanfaatan Eco Enzyme dalam Proses Biodrying Limbah Gambir (Uncaria Gambir Roxb) pada Kelompok Tani Bunga Gambir di Kecamatan Mungka - Rivo Yulse Viza; Veronika Sriwulantari; Rovel Lando Fambari (Yayasan Literasi Sains Indonesia, 2025)
Mungka District in Lima Puluh Kota Regency, West Sumatra, is one of the main centers of gambier production that generates a large amount of solid waste from the leaf pressing process. This waste had previously been unmanaged and posed an environmental pollution risk. This community service program aimed to implement bio drying technology based on eco enzym as an environmentally friendly solution to convert gambier pressing waste into value-added organic compost. The program was carried out collaboratively with the Bunga Gambir Farmers Group through training, demonstration, and field mentoring. The partners successfully produced eco enzym from household organic materials and applied it in the bio drying process. The activity resulted in a reduction of waste volume and moisture content by up to 70%, a color change to dark brown, odor reduction, and the formation of semi-mature compost with crumbly texture and no unpleasant odor. The compost product is currently being matured and evaluated for quality before field application. This program improved the knowledge, technical skills, and awareness of the farmers in sustainable waste management and established a practical model for eco enzym–based gambier waste processing that can be replicated in other rural communities.